From fiction to reality: reflections surrounding fictional characters - Agüero Miñano, Maritza Yesenia (2015)
The growth and development of worldwide products and services containing fictional characters has been exponential due to development, among others, of technology. This article examines the protection of fictional characters through copyright and reflects on its legal treatment.